2014
DOI: 10.1111/jasp.12225
|View full text |Cite
|
Sign up to set email alerts
|

Changing prejudiced attitudes by thinking about persuasive messages: implications for resistance

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in: El acceso a la versión del editor puede requerir la suscripción del recurso Access to the published version may require subscription Changing Prejudiced Attitudes by Thinking About Persuasive Messages: Implications for ResistanceMiguel A. M. Cárdaba Villanueva Centro UniversitarioPablo Briñol, Javier Horcajo Universidad Autónoma de MadridRichard E. Petty This research showed that changing attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 43 publications
0
10
0
1
Order By: Relevance
“…Debido a su alta correlación interna (alpha de Cronbach de .82) estos cuatro ítems fueron promediados para formar un único índice de actitudes hacia el producto. Mayores puntuaciones en este índice indicaron actitudes más positivas hacia el producto (para una medida similar de las actitudes, véase Briñol, Petty, y Stavraki, 2012;Cárdaba, Briñol, Horcajo, y Petty, 2014).…”
Section: Variables Dependientesunclassified
“…Debido a su alta correlación interna (alpha de Cronbach de .82) estos cuatro ítems fueron promediados para formar un único índice de actitudes hacia el producto. Mayores puntuaciones en este índice indicaron actitudes más positivas hacia el producto (para una medida similar de las actitudes, véase Briñol, Petty, y Stavraki, 2012;Cárdaba, Briñol, Horcajo, y Petty, 2014).…”
Section: Variables Dependientesunclassified
“…As expected, a 2 × 2 ANOVA showed only the predicted significant main effect of the elaboration manipulation on this index: participants in the high-elaboration condition reported greater cognitive effort (M = 7.35, SD = 1.39) than participants in the low-elaboration condition (M = 6.43, SD = 1.05), F 1, 61 = 8.17, p < .01, η 2 = .12. Although this might not be a perfectly reliable measure of amount of elaboration, previous research has shown that such self-reports can be effective in discriminating participants who had engaged in relatively high versus low elaboration (Cárdaba et al, 2014;.…”
Section: Notesmentioning
confidence: 96%
“…These second messages were briefer versions of the essays used for the first messages to avoid participants' fatigue, including only three arguments from the five arguments included in the first antilegalization or prolegalization message. In both cases, to hide the objectives of the experiment, these attacking counter-attitudinal messages (against or in favor of legalization) were presented as information published in newspapers (see Cárdaba et al, 2014).…”
Section: Direction Of the Second Messagementioning
confidence: 99%
“…Second, even if two different processes result in the same extent of persuasion, the consequences of this persuasion can differ. As noted earlier, the ELM holds that the process by which an attitude is formed or changed is consequential for the strength of the attitude (i.e., whether it lasts in the long term; see Cárdaba, Briñol, Horcajo, & Petty, ). For example, in a recent study, Mello, Garcia‐Marques, Briñol, Cancela, and Petty () found that attitudes predicted behavioural intentions better for those high (vs. low) in perceived attractiveness and that this effect was more likely to be observed for participants high (vs. low) in self‐objectification.…”
Section: Part Iii: Conclusion and Interventionsmentioning
confidence: 97%